Implementation of Tarjih Decisions on Prayer Worship Among Muhammadiyah Family Children in Jakarta Special Capital Region - Fakhrurazi Fakhrurazi; Masyitoh Masyitoh; Sopa Sopa; Saiful Bahri; Muhammad Misbakul Munir (PT Publikasiku Academic Solution, 2025)
This study aims to analyze the implementation of the Muhammadiyah Tarjih Decision on prayer in children's education in the Muhammadiyah family in the Special Capital Region of Jakarta. By using a descriptive qualitative approach through interviews, observations, and literature studies, this study found that the understanding of the Muhammadiyah family, especially the cadres and leaders, of the Tarjih Decision on prayer was good and they practiced it in their daily lives. The implementation of prayer education is carried out in two forms, namely the practice of prayer according to tarjih by teaching reading, memorization, and the example of parents, as well as the cultivation of spiritual, moral, and social values through prayer. The factors that support the success of the implementation are the relatively high level of education and family economy, while the obstacles faced are the limited access to Muhammadiyah educational facilities, so that some children study outside Muhammadiyah schools and are faced with different worship procedures. This research contributes to the development of Islamic education in the Muhammadiyah family and strengthens the implementation of the Tarjih Decision in urban communities.